Sustainable school leadership : portraits of individuality - Bottery, Mike; Wong, Ping-man; Ngai, George (Bloomsbury Academic, an imprint of Bloomsbury Publishing Plc, 2018)
"We live in a complex age, with multiple challenges to the practice of educational leadership, and where there is widespread evidence of individuals wanting to retire early from leadership positions, and of fewer wishing to take up the role. This highly experienced team of cross-cultural researchers combine scholarly research with over a decade of extensive empirical research using an innovative 'portrait' methodology to investigate the challenges that educational leaders on two continents currently face. The kinds of challenges described include: the personal (e.g. being new to the job, coping with the role, approaching retirement), the inter-personal (e.g. power relations, personal challenges with staff, parents and children), the local (e.g. issues faced by the school in the community), the national (e.g. government initiatives, inspection), the global (e.g. the impact of economic forces on political and institutional management). Sustainable School Leadership, then, contributes to the field of educational leadership in several ways. First, the authors bring scholarly enquiry to life by providing detailed descriptions of the challenges which individual educational leaders face in different cultures in a globalised world. Second, they show how the combined insights from individual portraits provide important and meaningful critiques of national policies and organizational functioning. Such critiques can then inform current and future leadership research through a better understanding of how links between the micro-, meso-, and macro-levels of education promote or discourage school leaders' sustainability. Finally, the authors present important cross-cultural comparisons of eastern and western approaches to educational leadership, suggesting that sustainability ¿ or a lack of it ¿ may have different roots in different cultures. Sustainable School Leadership is relevant to students on educational leadership and management courses, academics and researchers and school leaders."--Bloomsbury Publishing